Isolation and Molecular Characterization of Extended Spectrum Beta-lactamase (ESBL) Producing Escherichia Coli from Dogs - Singaravelan, Tamilarasu; Antony, Prabhaker X.; Vasu, Jayalakshmi; Srinivas, Mouttou V.; Shanmugam, Venkatesa P.; Shanmugam, Selvi; Darmalingam, Selvi; Mukhopadhyay, Hirak K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was aimed to isolate and characterize the Extended Spectrum Beta-lactamase (ESBL) producing Escherichia coli from faecal samples of dogs in Puducherry, India. In this study, 100 E. coli isolates were obtained from 50 healthy dogs and 50 diarrheic dogs, out of which 33 (33%) isolates were confirmed as ESBL producers by the combination disc method. All the E. coli isolates were genotypically confirmed for the presence of genes responsible for ESBL production. Out of 100 E. coli isolates, fourteen (14%), seven (7%) and three (3%) isolates were found to be positive for blaTEM, SHV and CTX-M genes, respectively. The present study highlighted ESBL-producing E. coli in dogs in Puducherry region.